Solution assembly MoS2 nanopetals/GaAs n–n homotype heterojunction with ultrafast and low noise photoresponse using graphene as carrier collector. Issue 1 (5th December 2016) - Zhang, Yan; Yu, Yongqiang; Wang, Xiaoyan; Tong, Guoqing; Mi, Longfei; Zhu, Zhifeng; Geng, Xiangshun; Jiang, Yang
Abstract : A MoS2 nanopetal/GaAs homotype heterojunction with ultrafast and low noise photoresponse was solution assembled using graphene as the carrier collector. Abstract : MoS2, the classical representative of layered structure transition metal dichalcogenides (TMDCs), has been widely used as an ideal n-type semiconductor, offering an interesting opportunity to construct heterostructures with other 2D layered or 3D bulk materials for ultrafast optoelectronic applications. In this work, we report the synthesis of ultrathin MoS2 nanopetals via a solution-processable route, and the solution assembly of a 2D MoS2 nanopetal/GaAs n–n homotype heterojunction using graphene as the carrier collector. The fabricated devices have excellent photoresponse characteristics including a good detectivity of ∼2.28 × 10 11 Jones, a noise current approaching 0.015 pA Hz −1/2 at zero bias and notably a very fast response speed, up to ∼1.87/3.53 μs with a broad photoresponse range. More interestingly, the device could respond to fast pulsed illumination up to 1 MHz, far exceeding the performance of many current congeneric 2D nanostructured and solution-processable photodetectors reported. These results suggest that our devices, together with the solution assembly methodology of the device described herein, can be utilized to give large-scale integration of low-cost, high-performance photodetectors, thus opening up new possibilities for 2D layered material-based photovoltaic and optoelectronic applications in the future.